Paranoia, Power and the Postmodern Feminism: A Comparative Study of Thomas Pynchon and Katherine Dunn in the Heroine’s Mode - Moebid, Abdulkareem Jwaid (Researchparks Publishing, 2026)
This article examines the ways in which The Crying of Lot 49 by Thomas Pynchon and Geek Love by Katherine Dunn deploy paranoia, corporeal marginality, and narrative disorder as forms of feminist resistance in postmodern literature. Where conventional literary theory concentrates on linear masculine quests and stable identities, these novels break with that pattern by reframing the Heroine’s Journey around descent, dark night, and interpretive obscurity. Utilizing feminist narratology, postmodernist theory, and qualitative thematic analysis, the article utilizes seven complementary themes–feminist paranoia, bodily marginalization, patriarchal constructs, the Heroine’s Journey, community identity, epistemic indeterminacy, and subversive agency–to compare the two novels. Analysis is informed by close readings, annotated text examples and theoretical memoing. The findings suggest that Oedipa Maas and Olympia Binewski resist patriarchy by not recognising or mastering it, but by remaining ambiguous and disruptive. Oedipa’s search for meaning becomes an act of epistemic resistance; her paranoia is interpretive agency, not delusion. By the same token, Olympia's marked body and halting narration turn abjection into understanding, reconfiguring maternal authorship and transgression as narrative strategies. Instead of registering a failure of form, the nonlinear, fragmented form of these novels exemplifies a feminist epistemology that prefers doubt, survival and embodied knowledge to coherence. Postmodern tropes—conspiracy, grotesquery, exile—are thus reappropriated as political and ethical instruments for feminist reworlding. Ultimately, paranoia and narrative instability are reframed as cognitive strategies of resistance. The female protagonists do not seek closure, but cultivate ambiguity as a means of survival and reinterpretation. This study contributes to feminist literary scholarship by showing how postmodern form becomes an ally in constructing subversive female identities and counter-epistemologies.